Flowmetering based on fluid oscillations phenomenon - Wee, Kok Seng. (2009)
When a confined rectangular jet hits a target placed in its flow path, it can be made to oscillate about the two sides of the target. The oscillation frequency is a function of the flow rate. This phenomenon is used in the development of a flowmeter, called a target flowmeter. Such a flowmeter needs no calibration and has the potential of measuring a wide range of flow rates. In addition, it is suitable for remote and automatic monitoring of volume flow rate since its output signals are electrical pulses. This is extremely useful for domestic gas and water metering.